Medium-term Impact of Conservation Agriculture on Soil Organic Carbon and Water Stable Aggregates in a Rainfed Hilly Agro-ecosystem - Mishra, K. N.; Tripathy, Bidyashree; Roul, P. K.; Dash, S. N. (International Journal of Bio-resource and Stress Management, 2023)
The impact of conservation agriculture production system (CAPS) on soil organic carbon, bulk density, water stable aggregates and dry season soil moisture content across the profile (0−5, 5−10 and 10−20 cm) was assessed at the end of the 3rd cropping year in the rainfed agro-ecosystem under the hilly tracts of north Odisha. The treatment combinations are conventional tillage (CT) and minimum tillage (MT) with sole maize (M) and inter cropmaize+cowpea (M+C) in main-plots during wet season and horse gram (H), Toria mustard (T) and no cover crop (NCC) in sub-plots during dry season. Surface accumulation and retention of soil organic matter (SOM) under MT decreased the bulk density (BD) by 3.4%, 2.6%, increased the soil organic carbon (SOC) by 27.9%, 15.2%, water stable macro-aggregates by 14.9%, 11.9%, macro-aggregate C by 5.2%, 4.3% over the initial status in the top two layers (0−5, 5−10 cm). Depletion of SOM induced by soil inversion under CT systems increased the BD (+1.5%, +2.2%), decreased the SOC (-9.8%, -15.7%) and macro-aggregates (-5.3%, -5.7%). The pronounced effect of cover crops due to litter inputs was reflected on SOC (+13.0%) and macro-aggregates (+7.2%) in the surface layer of 0−5 cm. Higher SOC stratification ratio observed in the soils under MT (1.73 to 1.79) indicated the effectiveness of MT in improving SOM accumulation. The study singles out SOC as the most dominant soil parameter affecting soil BD (r =-0.85**), water stable macro-aggregates (r=0.90**), macro-aggregate C (r=0.92**) and soil moisture (r=0.82**) in the surface layer.